Impact of esophageal mucosal permeability markers on provocation‐induced esophageal reflexes in high‐risk infants. Issue 12 (27th June 2022) - Jadcherla, Sudarshan R.; Helmick, Roseanna; Hasenstab, Kathryn A.; Njeh, Minna; Alshaikh, Enas
Abstract: Esophageal distal baseline impedance (DBI) is an indicator of mucosal integrity; lower values suggest increased permeability. Aims were to characterize the (1) effect of DBI category (<900 Ω, 900–2000 Ω, and >2000 Ω) on sensory‐motor characteristics of mid‐esophageal provocation‐induced motility reflexes, and (2) clinical outcomes among high‐risk human infants evaluated for gastroesophageal reflux disease. Symptomatic infants ( N  = 49, 41 ± 3 weeks postmenstrual age) underwent pH‐impedance testing to characterize acid reflux index (ARI) and DBI, and pharyngo‐esophageal manometry to examine upper esophageal sphincter (UES), peristaltic, and lower esophageal sphincter (LES) functions. Sensory‐motor response characteristics included response threshold (ml), occurrence (%), latency (s), duration (s), and magnitude (mmHg) upon mid‐esophageal stimulations (0.1–2.0 ml of air, water, and apple juice). Motility and clinical outcomes were compared among DBI groups. In infants with DBI <900 Ω and 900–2000 Ω (vs. >2000 Ω): (a) Long‐term feeding milestones did not differ ( p  > 0.05); (b) complete peristaltic propagation decreased in 900–2000 Ω ( p  < 0.05), polymorphic waveforms increased in <900 Ω and 900–2000 Ω ( p  < 0.05); (c) media effects were noted with liquids (vs. air) wherein UES and esophageal contractility were prolonged in <900 Ω and 900–2000 Ω ( p  < 0.05), and esophageal sensitivity heightened for <900 Ω with water and for 900–2000 Ω with air (both p  < 0.05). ARI was not correlated with DBI in infants with chronic lung disease ( r  = 0.05, p  = 0.82). We conclude that pharyngo‐esophageal motility sensory‐motor characteristics in infants are modified by DBI category. These preliminary findings pave‐the‐way for further physiological testing in convalescing high‐risk infants to ascertain potential mechanisms of airway‐digestive reflex interactions and symptom generation, which may lead to targeted therapies.